2008
DOI: 10.1294/jes.19.35
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a High Dose Combination of PMSG/hCG Preparation of Mares Clinically Diagnosed with Ovarian Quiescence during the Breeding Season (Investigation from 1975 to 2000)

Abstract: A total of 88 thoroughbred mares were diagnosed with clinical ovarian quiescence and subjected to four treatment regimens. Using PMSG, hCG or combinations of both. A high dose combination of 5,000IU PMSG with 5,000IU hCG showed significantly higher rates of marked estrus and ovulation induction (P<0.01) as well as conception rates (P<0.05). In the present study, the administration of a high-dose combination of PMSG with hCG was shown to be an effective treatment of ovarian quiescence in light mares.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The results of the present study showed that a high dose of PMGS/hCG combination induced follicular growth and ovulation in anestrous mares. This is in agreement with a study on Hokaido, Japan (Tsukada et al, 2008) which used 5000 IU of PMSG and 5000 IU of hCG to treat ovarian quiescence in mares. However, previous studies (Woods et al, 1982;Palmer et al, 1993) indicated that low dose PMSG did not affect follicle development in mares.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study showed that a high dose of PMGS/hCG combination induced follicular growth and ovulation in anestrous mares. This is in agreement with a study on Hokaido, Japan (Tsukada et al, 2008) which used 5000 IU of PMSG and 5000 IU of hCG to treat ovarian quiescence in mares. However, previous studies (Woods et al, 1982;Palmer et al, 1993) indicated that low dose PMSG did not affect follicle development in mares.…”
Section: Discussionsupporting
confidence: 91%